Prisoner and ex-prisoner health: Improving access to primary care - Kinner, S.; Streitberg, L.; Butler, Tony; Levy, M. (2012)
Prisoners have markedly elevated rates of mental illness, chronic disease, substance dependence and engagement in health risk behaviours. The prison setting provides a unique opportunity to address the physical and mental health needs of this disadvantaged group. However, any benefits gained by prisoners from contact with prison health services are often lost once they return to the community. This article outlines the health inequalities experienced by prisoners and ex-prisoners in Australia, describes the community health centre operating at the Alexander Maconochie Centre in Canberra, and provides practical suggestions for improving access to primary care for this population, both in custody and after return to the community.